2016
DOI: 10.1088/0143-0807/38/1/019401
|View full text |Cite
|
Sign up to set email alerts
|

Four easy routes to the Lorentz transformations: addendum to ‘Lorentz transformations and the wave equation’

Abstract: In this paper I briefly discuss and compare four easy derivations of the Lorentz transformations. Two of these derivations assume the invariance of the Minkowski spacetime interval in inertial frames and the other two assume the invariance of the d'Alembert operator in these frames. These derivations are suitable for a first view of special relativity. Finally, I discuss the comment made by Di Rocco on my original paper, 'Lorentz transformations and the wave equation' (2016 Eur. J. Phys. 37 025603).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…An observer from S will agree about the monochromatic aspect of the wave emitted by the source from S (see e.g. [26][27][28] in this context). But there is no reason to agree on the angle of emission θ or on its frequency ν 0 (and implicitly on its wavelength λ).…”
Section: Appendix a Relativistic Doppler Shiftmentioning
confidence: 99%
“…An observer from S will agree about the monochromatic aspect of the wave emitted by the source from S (see e.g. [26][27][28] in this context). But there is no reason to agree on the angle of emission θ or on its frequency ν 0 (and implicitly on its wavelength λ).…”
Section: Appendix a Relativistic Doppler Shiftmentioning
confidence: 99%
“…2 1 There will be, therefore, a limit for the speed v of the S′ frame with respect to the S frame in order for x′ and t′ to remain real. Calling this unspecified limiting speed V, where = -V n , 2 1 transformation (1a) now becomes the Ignatowsky transformation:…”
Section: Derivation Of the Relativistic Transformations In Four Stepsmentioning
confidence: 99%
“…Recent papers in this journal [1][2][3][4] and elsewhere [5] have shown that considerable interest remains in the various methods of deriving the Lorentz [6] transformation of special relativity. Of these, Heras' [1] more recent paper must surely win the prize for the most new derivations (four) in one paper, these being derived from established laws of physics which are known to be relativistic, as in his earlier paper [2]. Chao [3] used symmetry to improve Einstein's derivation.…”
Section: Introductionmentioning
confidence: 99%